2014
DOI: 10.1186/1824-7288-40-50
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life and disease severity in Hungarian children and young adults with cystic fibrosis

Abstract: BackgroundThe aim of our study was to evaluate factors affecting cystic fibrosis (CF) patients’ health-related quality of life (HRQoL) and to assess the level of agreement on HRQol between children and their parents.MethodsFifty-nine patients (mean age: 14.03 ± 4.81 years) from 5 Hungarian CF centres completed the survey. HRQoL was measured using The Cystic Fibrosis Questionnaire-Revised (CFQ-R). Parents were asked to fill out a questionnaire about their smoking habits, educational level and history of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 25 publications
6
51
0
3
Order By: Relevance
“…The positive association between scores in Respiration domain and spirometry [16] have also been previously reported [16,26], thereby validating CFQ-14+ showing correlation between pulmonary function and Respiration domain. Similar to our study, an Italian study also found lower Respiration scores for Pseudomonas positive, compared to negative patients [19].…”
Section: Fig 1 a Correlation Between Hrqol Scores (Adolescent's Formsupporting
confidence: 85%
See 1 more Smart Citation
“…The positive association between scores in Respiration domain and spirometry [16] have also been previously reported [16,26], thereby validating CFQ-14+ showing correlation between pulmonary function and Respiration domain. Similar to our study, an Italian study also found lower Respiration scores for Pseudomonas positive, compared to negative patients [19].…”
Section: Fig 1 a Correlation Between Hrqol Scores (Adolescent's Formsupporting
confidence: 85%
“…The CFQ-R is the only patient-reported outcome instrument with versions for both children and the caregivers. It has been translated into 34 languages all over the world [17][18][19][20][21]. Our objective was to use CFQ-R to assess Quality of Life (QoL) in Indian children with CF.…”
mentioning
confidence: 99%
“…HRQOL was measured using the Cystic Fibrosis Questionnaire-Revised (CFQ-R). The CFQ-R is a widely used, validated, disease-specific instrument for HRQOL measurement in patients with cystic fibrosis [12][13][14][15][16]. The Hungarian and Polish [17] versions of the CFQ-R were used to assess HRQOL from patients' (patient-report) and their parents' perspectives (parent-proxy report).…”
Section: Instruments Used In the Studymentioning
confidence: 99%
“…However, Pseudomonas aeruginosa infection in CF patients remains a major problem, with a negative impact both on overall survival and Quality of Life (QoL) [2,3,4]. …”
Section: Introductionmentioning
confidence: 99%